Prevalence of crt and mdr-1 mutations in Plasmodium falciparum isolates from Grande Comore island after withdrawal of chloroquine. (December 2016) - Huang, Bo; Wang, Qi; Deng, Changsheng; Wang, Jianhua; Yang, Tao; Huang, Shiguang; Su, Xin-zhuan; Liu, Yajun; Pan, Longhua; Li, Guoming; Li, Di; Zhang, Hongying; et al.
Abstract Background In Comoros, the widespread of chloroquine (CQ)-resistantPlasmodium falciparum populations was a major obstacle to malaria control, which led to the official withdrawal of CQ in 2004. Continuous monitoring of CQ-resistant markers of theP. falciparum CQ resistant transporter (pfcrt ) and theP. falciparum multiple drug resistance 1 (pfmdr -1 ) is necessary inder to obtain first-hand information on CQ susceptibility of parasite populations in the field. The objective of this study is to assess the prevalence and evolution of CQ-resistance in theP. falciparum populations on the Comoros' Grande Comore island after withdrawal of CQ. Methods A total of 207P. falciparum clinical isolates were collected from the island, including 118 samples from 2006 to 2007 and 89 samples from 2013 to 2014. Nucleotide substitutions in thepfcrt andpfmdr -1 genes linked to CQ response in parasite isolates were assessed using nested PCR and DNA sequencing. Results From thepfcrt gene segment sequenced, we detected C72S, M74I, N75E, and K76T substitutions in the parasite isolates collected from both 2006– 2007 to 2013– 2014 periods. Significant decline ofpfcrt resistant alleles at C72S (42.6 to 6.9 %), M74I (39.1 to 14.9 %), N75E (63.5 to 18.3 %), and K76T (72.2 to 19.5 %) from 2006–2007 to 2013–2014 were observed, and the frequency ofpfcrt wild type allele was significantly increased from 19.1 % in 2006–2007 to 75.8 % in 2013–2014. Sequence analysis ofpfmdr -1 also detected point mutations at codons N86Y, Y184F, and D1246Y, but not S1034C and N1042D, in the isolates collected from both examined periods. An increasing trend in the prevalence of thepfmdr -1 wild type allele (NYD, 4.3 % in 2006–2007; and 28.7 % in 2013–2014), and a decreasing trend forpfmdr -1 N86Y mutation (87.0 % in 2006–2007; and 40.2 % in 2013–2014) were observed in our samples. Conclusions The present data indicate that the prevalence and patterns of mutantpfcrt andpfmdr -1 dramatically decreased in the Grande Comore isolates from 2006 to 2014, suggesting that the CQ-sensitiveP. falciparum strains have returned after the withdrawal of CQ. The data also suggests that the parasites with wild typepfcrt /pfdmr -1 genes may have growth and/or transmission advantages over the mutant parasites. The information obtained from this study will be useful for developing and updating anti-malarial treatment policy in Grande Comore island.